Media and identity in Africa - Middleton, John, 1921-2009; Njogu, Kimani (International African seminars ;, 2009)
Studies of the media in Africa, incorporating both African and international perspectives, are few. The thirty papers collected here were presented at a seminar organised and hosted by the Kenya-based Twaweza Communications and the International African Institute in Nairobi in 2004. They demonstrate how media outlets are used to perpetuate, question or modify the unequal power relations between the North and the South. Focusing on east Africa, the papers include discussions of the construction of old and new social entities, as defined by class, gender, ethnicity, political and economic differences, wealth, poverty, cultural behaviour, language and religion. The authors illustrate how there is increasing control by local people of traditional and modern forms of media. Globalization is being countered by local responses, within the context of social and cultural identities. Essentially, the book describes the tensions between the global and the local, tensions not often discussed in media studies, thus pioneering new debates.